Solution structure of pleckstrin homology domain of dynamin by heteronuclear NMR spectroscopy. - Fushman, D (1995)
The pleckstrin homology (PH) domain is a recognition motif thought to be involved in signal-transduction pathways controlled by a variety of cytoplasmic proteins. Assignments of nearly all 1H, 13C, and 15N resonances of the PH domain from dynamin have been obtained from homonuclear and heteronuclear NMR experiments. The secondary structure has been elucidated from the pattern of nuclear Overhauser enhancements, from 13C chemical shift deviations, and from observation of slowly exchanging amide hydrogens. The secondary structure contains one alpha-helix and eight beta-strands, seven of which are arranged in two contiguous, antiparallel beta-sheets. The structure is monomeric, in contrast to the well-defined intimate dimerization of the crystal structure of this molecule. Residues possibly involved in ligand binding are in apparently flexible loops. Steady-state 15N(1H) nuclear Overhauser effect measurements indicate unequivocally the boundaries of this PH domain, and the structured portion of the domain appears to be more extended to the C terminus than previously suggested for other PH domains.